2021
DOI: 10.4049/jimmunol.2001282
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Regulation of Cytokine Production following TLR3 Engagement in Murine Bone Marrow–Derived Macrophages Is Dependent on Viral Nucleic Acid Length and Glucose Availability

Abstract: Hypoxia-inducible factor-1α (HIF-1α) is an important regulator of glucose metabolism and inflammatory cytokine production in innate immune responses. Viruses modulate HIF-1α to support viral replication and the survival of infected cells, but it is unclear if this transcription factor also plays an important role in regulating antiviral immune responses. In this study, we found that short and long dsRNA differentially engage TLR3, inducing distinct levels of proinflammatory cytokine production (TNF-α and IL-6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 120 publications
0
1
0
Order By: Relevance
“…The occurrence of this coordination effect depends on the gene expression of HIF-1α, and its multiple downstream cytokines play an important role in angiogenesis, bone regeneration and bone remodeling ( Miclau et al, 2017 , Wilson, Wong, Toupadakis, & Yellowley, 2015 ). In recent years, studies have reported that HIF-1α contributes to the healing of osteoporotic fractures and the recovery of various bone diseases ( Ahmed et al, 2021 , Hirai et al, 2018 , Silagi, Schipani, Shapiro, & Risbud, 2021 , Tian et al, 2022 , Wang et al, 2021 , Wang et al, 2021 , Wang et al, 2021 , Zhang et al, 2022 , Zhao et al, 2021 ). At the same time, it can promote bone regeneration and protect bone cells ( Xu et al, 2021 , Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of this coordination effect depends on the gene expression of HIF-1α, and its multiple downstream cytokines play an important role in angiogenesis, bone regeneration and bone remodeling ( Miclau et al, 2017 , Wilson, Wong, Toupadakis, & Yellowley, 2015 ). In recent years, studies have reported that HIF-1α contributes to the healing of osteoporotic fractures and the recovery of various bone diseases ( Ahmed et al, 2021 , Hirai et al, 2018 , Silagi, Schipani, Shapiro, & Risbud, 2021 , Tian et al, 2022 , Wang et al, 2021 , Wang et al, 2021 , Wang et al, 2021 , Zhang et al, 2022 , Zhao et al, 2021 ). At the same time, it can promote bone regeneration and protect bone cells ( Xu et al, 2021 , Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%